the effect of different doses of silymarin on gentamicin induced kidney damage in rats - Al-shawi, nada. Naji; rehman hussain, saad abdel; AH, husam hasson; rashid, yahia zeki; numan, nawfal abdel munim (Journal of the Faculty of Medicine Baghdad, 2005)
Background: